Performing National Identity - Blažević, Zrinka (2001)
The historiographical writings of the Baroque polymath Pavao Ritter Vitezovic (1652-1713), following immediately on the Karlowitz peace treaty (1699), have been included in the canon of "basic works of Croatian national politics" by the traditional nineteenth century historiography. The question therefore arises which symbolic models, ideological concepts and narrative constructions of his discourse seemed to be "state-making" and "nation-making" within the interpretative framework of "national" historiography. I shall try to show how Vitezovic&#8217 ; ; ; s performative historiographical discourse (Bourdieu) produces such an effect, and demonstrate how this discourse, using its signifying resources, creates and makes legitimate the symbolic construction of national identity, creating a virtual, utopian artefact - a "revived Croatia." However, even though mechanisms, strategies and devices accounting for its internal cohesion and persuasiveness can be identified in the dominant semantic layer of this performative discourse, it at the same time lends itself to an analysis exposing its "burried grammar" of internal contradictions, mostly contextually determined, destabilising and disintegrating it. This of necessity makes the "national" reading reductive, proposing instead canonical texts as polyphonic cultural artefacts bearing imprints of various discoursive and contextual reinscriptions. As Vitezovic&#8217 ; ; ; s case will, I hope, demonstrate, the early modern textual "articulations of national identity" carry a "surpluss of meaning" transcending its immediate temporal and cultural context, therby making it resistent to interpretative stabilising and ensuring its continuing existence and multiplication of its interpretative "performance."